The Relationship of Learning Motivation With The Biology Learning Outcomes in Senior High School - Rezita, Nora; Sari , Rona Taula; Har, Erman; Deswati , Lisa (Universitas Veteran Bangun Nusantara Sukoharjo, 2023)
This study aims to determine the relationship between motivation and learning outcomes of biology in class XI MIPA SMAN 1 Luhak Nan Duo, West Pasaman Regency. In the learning process, motivation plays an important role, especially student learning outcomes. This type of research is descriptive with quantitative research methods. The research was conducted at SMAN 1 Luhak Nan Duo, West Pasaman Regency with a population of 126 students of class XI MIPA enrolled in the odd semester of the academic year 2021/2022, with a sample of 94 students. The sampling technique was simple random sampling which was carried out randomly, using a significance of = 5%. The data collection in this study used a questionnaire containing statements of student learning motivation using a Likert scale, odd mid-semester exam scores for the 2021/2022 academic year. The results of the Pearson product moment correlation test are 0.611 (61.1%) on extrinsic motivation (X1) and intrinsic motivation (X2) of 0.505 (50.5)%, meaning that there is a fairly strong relationship between extrinsic motivation (X1) and intrinsic motivation. (X2) with the results of learning biology in class XI MIPA SMAN 1 Luhak Nan Duo, West Pasaman Regency. The results of the t-test showed that the t-count of extrinsic motivation (X1) was 7.410 and the t-count of intrinsic motivation (X2) was 5.618 indicating that there was a significant relationship. The coefficient of determination of extrinsic motivation (X1) is 37.4% and intrinsic motivation (X2) is 25.5%, this means that extrinsic motivation (X1) and intrinsic motivation (X2) contribute to student biology learning outcomes (Y).